Antiproliferative Properties of 7,8-Ethylene Diamine Chelator-Lipophilic Fluoroquinolone Derivatives Against Colorectal Cancer Cell Lines - Khaleel, Sara; Al-Hiari, Yusuf; Kasabri, Violet; Haddadin, Randa; Albashiti, Rabab; Al-Zweri, Muhammad; Bustanji, Yasser (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Cancer is one of the most overwhelming diseases nowadays. It is considered the second cause of death after cardiovascular diseases. Due to the diversity of its types, stages and genetic origin, there is no available drug to treat all cancers. Serious side effects and resistance of existing drugs are other problems in the struggle against cancer. In such quest, fluoroquinolones (FQs) promising as antiproliferative compounds due to safety, low cost and lack of resistance. Objectives: Therefore, this work aims at developing lipophilic FQs and screening their antiproliferative activity against colorectal cancer. Methods: Nine prepared FQs were investigated for antiproliferative activity utilizing in vitro SRB method. In comparison to the antiproliferative agent cisplatin; the assessment of antiproliferative activities of these novel FQs in a panel of Colorectal Cancer Cell (CRC) lines (HT29, HCT116, SW620, CACO2, SW480) and normal periodontal ligament fibroblasts for safety examination was performed. Antibacterial activity (MIC) was conducted against Staphylococcus aureus and Escherichia coli standard strains using the broth double dilution method. Antioxidant properties were suspected as the mechanism of antiproliferative activity; thus, a DPPH test was performed to analyze radical scavenging potency of FQs compared to ascorbic acid as reference agent. FQs compounds 3-5(a-c) were prepared, characterized and their structure was confirmed using spectroscopy techniques. Results: All compounds manifested good to excellent antiproliferative activity on HT29, HCT116, and SW620 with high safety index. The reduced series 4a, 4b and 4c exerted excellent micro to nano -molar antiproliferative activities on HT29, HCT116, and SW620 which were stronger than the reference cisplatin against all cells. The reduced group of compounds 4(a-c) revealed higher potency vs. both nitro and triazolo groups. On cell lines HT29, HCT116, and SW620, reduced 4a with 7,8-ethylene diamine,the substitution revealed the highest antiproliferative efficacy (IC50 value) approaching nano molar affinity with higher safety vs. cisplatin. The most active compound, 4a, exhibited significant potency against HCT116, and SW620 with IC50 0.6 and 0.16 μM respectively. Novel FQs (4a, 4b and 4c) also showed strong radical scavenging activity with IC50 values (μM) 0.06, 23, and 7.99, respectively. Exquisitely 4a revealed a similar pattern of activity to doxorubicin, indicating a similar mechanism of action. Strong antiproliferative and weak antibacterial activities of series 4 endorse that their mechanism involves eukaryotic topoisomerase II inhibition. This work has revealed novel FQs with excellent anticancer activity against 5 colorectal cancer (HT29, HCT116, SW620, CACO2, SW480) cell lines with a potential chelation mechanism due to 7,8-ethylene diamine chelator bridge. Conclusion: The new FQs have confirmed that more lipophilic compounds could be more active as hypothesized. The p-halogenated aniline, N1-Butyl group in addition to 3-COOH, 8-NH2 are all essential requirements for strong antiproliferative FQ of our FQ scaffold. This work emphasizes the role of C-8 amino as part of ethylene diamine group as an essential requirement for antiproliferative FQs for the first time in the literature, entailing its role toward potential antineoplastic FQs.
Keywords: fluoroquinolones